ANALYSIS OF SUBSIDY FERTILIZER POLICY ON FARMERS SATISFACTION IN DELI SERDANG DISTRICT - Khoirul Imami Sitorus; Jafar Syahbuddin Ritonga; Ahmad Rafiki (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2023)
This study aims to find out how. subsidized fertilizer policy on farmer satisfaction in Deli Serdang Regency, this study took place in Tanjung Rejo Village, Percut Sei Tuan District, Deli Serdang Regency. The form of this research was descriptive quantitative research. The population in this study were all rice farmers in Tanjung Village. Rejo District of Percut Sei Tuan, Deli Serdang Regency as many as 2288 farmers, the sample used was the slovin technique with a total sample of 100 people, the data analysis technique used in this study was multiple linear regression analysis, while the results of this study were,A constant value of 30,074 indicates a positive constant value, meaning that if the Subsidized Fertilizer Price, Fertilizer Distribution Time, Distribution Place and Fertilizer Amount do not change or equal to 0 then it will increase farmer satisfaction by 30,074%, Partial test shows that Fertilizer Amount, Price Subsidized Fertilizers, and Fertilizer Distribution Time have an influence on farmer satisfaction, this is because the sig value <0.05, Place of Distribution has no effect on farmer satisfaction, this shows that if farmers do not get subsidized fertilizer they will look for other alternatives, R Square value of 0.543 or 54.3 % means that in this study the amount of fertilizer, the price of subsidized fertilizer, the place of distribution, the time of distribution of fertilizer contributed 54.3% to farmer satisfaction, while the remaining 45.7% is influenced by other factors not examined in this study such as government assistance, grain prices and yields